Functional fatigue and upper extremity sensorimotor system acuity in baseball athletes - Tripp, Brady L; Yochem, Eric M; Uhl, Timothy L (Journal of athletic training, 2007)
The sensorimotor system controls the balance between upper extremity stability and mobility during athletic performance. Research indicates that fatigue hampers sensorimotor system function; however, few investigators have studied functional fatigue or multijoint, multiplanar measures. To examine the effect of functional fatigue on upper extremity position reproduction in overhead throwing athletes. Single-session, repeated-measures design. University musculoskeletal laboratory. Sixteen healthy collegiate baseball players (age = 21.0 +/- 1.6 years, height = 175.8 +/- 10.2 cm, mass = 82.8 +/- 4.3 kg). Subjects threw a baseball from a single knee with maximum velocity (every 5 seconds) and rated their level of upper extremity exertion after every 20 throws. Subjects stopped after reporting above level 14 on the Borg scale and began posttests immediately. We measured active multijoint reproduction of 2 positions: arm cock and ball release. Dependent variables were absolute and variable error for 10 joint motions: scapulothoracic internal-external rotation, upward rotation, and posterior tilt; glenohumeral internal-external rotation, horizontal abduction-adduction, and flexion-extension; elbow pronation-supination and flexion-extension; and wrist ulnar-radial deviation and flexion-extension. We calculated acuity for each joint and the entire upper extremity using 3-dimensional variable error. Fatigue occurred after an average of 62 +/- 28 throws and increased 3-dimensional variable error scores (ie, decreased acuity) of the entire upper extremity and all joints in both positions (P < .05) except for the wrist in arm cock. Fatigue increased errors (ranging from 0.6 degrees to 2.3 degrees ) at arm cock for scapulothoracic internal-external rotation, upward rotation, and posterior tilt; glenohumeral internal-external rotation and flexion-extension; elbow flexion-extension; and wrist ulnar-radial deviation and at ball release for scapulothoracic internal-external rotation and upward rotation, glenohumeral horizontal abduction-adduction, elbow pronation-supination, and wrist ulnar-radial deviation and flexion-extension (P < .05). Functional fatigue affects the acuity of the entire upper extremity, each individual joint, and multiple joint motions in overhead throwers. Clinicians should consider the deleterious effects of upper extremity fatigue when designing injury prevention and rehabilitation programs and should incorporate multijoint and multiplanar endurance exercises. Compromised neuromuscular control of the scapulohumeral relationship may hold pathologic implications for this population as well.